Long-term risk of acute coronary syndrome in patients with cholangitis: A 13-year nationwide cohort study - Tsai, Ming-Shian; Li, Yu-Fen; Lin, Cheng-Li; Hsu, Yao-Chun; Lee, Po-Huang; Sung, Fung-Chang; Kao, Chia-Hung (European journal of internal medicine, 2014)
Patients with cholangitis may exhibit repeated and chronic inflammation of the biliary tract despite successful medical or surgical treatments. This nationwide cohort study examined the association between cholangitis and the subsequent development of acute coronary syndrome (ACS). We identified a cohort of 37676 patients who were diagnosed with cholangitis between January 1998 and December 2010, and a comparison cohort of 150704 subjects frequency matched by age, sex, and index year after excluding comorbidities for ACS. Both cohorts were followed until the end of 2010 to measure the incidence of ACS. Both incidence rate ratios and hazard ratios of ACS were estimated by age and sex. Sex-specific analysis showed that males were at a higher incidence of ACS than females in both groups with (16.2 vs 11.5 per 10000person-years) and without (18.7 vs 12.5 per 10000person-years) cholangitis. The incidence of ACS also increased with age no matter having or not having cholangitis. The age stratified analysis revealed that the risk of ACS was significantly higher in patients with cholangitis younger than 65years old. The multivariable Cox proportional hazard model demonstrated that cholangitis was significantly associated with ACS (adjusted hazard ratio [HR]=1.18; 95% confidence interval [CI], 1.03–1.35) after adjusting age and sex in the model. This study suggests that patients with cholangitis are at an elevated risk of ACS. Awareness of the potential ACS risk for patients with cholangitis is important for patients and clinicians. •Males were at a higher incidence of ACS than females.•The incidence of ACS increased with age.•Awareness of the ACS risk for cholangitis is important for patients and clinicians.